Anupana: The Silent Architect Of Ayurvedic Pharmacodynamics - Fathima, Noor; M, Spandana; Sahana, G S; S, Haripriya; M, Raghunath; Kumar K M, Anil; Kumar B G, Chethan (Journal of Neonatal Surgery, 2026)
ABSTRACT Ayurveda, the oldest living Medical Science, holds timeless knowledge that still guides healing today. It recognizes that treatment must suit the individual in the personalized approach and Anupana becomes an inseparable part of therapy. Anupana, the adjuvant administered along with or after medicine, is a classical Ayurvedic concept with potential implications for therapeutic precision. Despite extensive textual descriptions, its mechanistic and translational relevance remains underexplored.